Financial Forecasting as a Strategic Tool for Competitive Pricing Formulation in the Small-Scale Soy Sauce Industry - Murtini Murtini; Latiah Anom; Susilowati Rahayu; Eka Adiputra (Trescode Green Organization, 2026)
This study analyzes the application of financial forecasting in developing a competitive pricing strategy at Kecap X Small Industry. A qualitative research method was used by examining sales data from 2024 to 2025 and projecting sales for 2026 using the least square method. The results indicate a potential sales increase of 0.05% in 2025, supported by declining inflation trends and competitive price adjustments compared to competing products such as Kecap ABC, Bango, Sedap, and Indofood. The company is advised to optimize production cost efficiency through supply chain optimization and implement marketing strategies such as seasonal discounts and bundling packages to expand market reach. With an appropriate pricing strategy supported by comprehensive fundamental analysis, the profitability and market competitiveness of Kecap X Small Industry are expected to improve sustainably amidst dynamic market competition.